Qualitative and quantitative characteristics of different types of tumor microvessels depending on the histological type of cervical cancer - M. A. Senchukova; E. V. Makarova; E. I. Shurygina; N. N. Volchenko (Исследования и практика в медицине, 2020)
Purpose of the study. To give a qualitative and quantitative assessment of different types of tumor microvessels depending on the histological type of cervical cancer (CC).Material and methods. The tumor samples from 76 patients with CC stage I–IIA who received the surgical treatment on the first phase were the object of study. The immunohistochemical study was performed using antibodies to CD34 and podoplanin. Statistical analysis of the data was performed using the Statistica 6.0 software.Results. In CC, the following types of tumor microvessels have been identified: normal microvessels, dilated capillaries (DCs) with a normal endothelial lining, DCs with a weak expression of CD34, DCs of contact type, capillaries in the solid component of tumor, the atypical dilated capillaries (ADCs), the structures with partial endothelial lining and the lymphatic capillaries in lymphoid and polymorphic cell infiltrates. It was found that DCs with a mild expression of CD34 (p=0.0005), DCs of contact type (p=0.000005), and capillaries in the solid component of tumor (p=0.006) were correlated with the prognosis in early CC. The detection frequency of this tumor microvessels was lower in more prognostically favorable squamous non-keratinizing CC, while in the prognostically unfavorable squamous cell keratinizing CC and adenocarcinoma of the cervix uteri, the higher DCs values with a mild expression of CD34 (р=0,004 and р=0.005, respectively) and DC of contact type (p=0.02 and p=0.14, respectively) were typical.Conclusion. We consider it is expedient to further study the relationship of different types of tumor microvessels with clinical and morphological characteristics and prognosis of cervical cancer.